Effect of structured lipids as dietary supplements on the fatty acid profile, carcass yield, blood chemistry, and abdominal fat deposition of female broilers - Hongzeng Ai; Yee-Ying Lee; Yuxia Lu; Chin Ping Tan; Oi Ming Lai; Aijun Li; Yufei Zhang; Yong Wang; Zhen Zhang (Poultry Science)
An experiment was conducted to evalute the effects of adding palm olein (POL), modified palm olein (high degree of acyl migration palm olein, H-AMD), and lard (total fatty acid saturation degree is similar to palm olein) to the diet of broilers. The study assessed production performance, fatty acid absorption, and abdominal fat deposition. A total of 100 one-week-old female broiler chicks were randomly assigned to three-tiered pens and fed five experimental diets. Enzymatic interesterification of POL causes acyl migration, transforming 1-palmitoyl-2,3-dioleoyl-sn-glycerol (sn-POO) and 1,3-dipalmitoyl-2-oleoyl-sn-glycerol (sn-POP) into 1,3-dioleoyl-2-palmitoyl-sn-glycerol (sn-OPO) and 1,2-dipalmitoyl-3-oleoyl-sn-glycerol (sn-PPO), which increases the saturated fatty acid content at the sn-2 position. Feeding broilers with this modified oil has improved the absorption effect of saturated fatty acids and increased the content of palmitic acid in abdominal tissue by 1.55%-1.69%. The impact on the content and positional distribution of fatty acids deposited in the body is limited. Low-density lipoprotein cholesterol (LDL-C) levels decreased by 34%, while high-density lipoprotein cholesterol (HDL-C) levels increased by 23%, resulting in a lower risk of atherosclerosis. No significant differences have been observed in carcass yield results of the POL and H-AMD groups. Compared with animal-derived oils such as lard which are also rich in saturated fatty acids at the sn-2 position, plant-derived oils such as POL and its modified products have a smaller effect on abdominal fat deposition.